2015
DOI: 10.3109/02699052.2015.1071427
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of a stigmatized identity: A qualitative study of the reasons why people choose to tell or not tell others about their traumatic brain injury

Abstract: Disclosure can have important advantages and disadvantages. Some people with a TBI may need support in making optimal decisions about disclosure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
2
17
0
1
Order By: Relevance
“…Overall, Olney and Brockerman (2003) found that disclosure involves an "intricate decision-making process about revealing disability information". Riley and Hagger (2015) interviewed 10 people of various ages who had suffered from a traumatic brain injury. They identify six reasons for nondisclosure: fears of negative reactions from others, feelings of shame, avoidance of emotional upset about the incident causing the injury, feelings that others were not interested in their injury, perceptions that the stress of disclosing their injury to others outweighed the benefits and a desire to fit in as a person without a brain injury-or in other words, not wanting a traumatic brain injury to define them and to isolate them socially.…”
Section: Disability and Disclosurementioning
confidence: 99%
“…Overall, Olney and Brockerman (2003) found that disclosure involves an "intricate decision-making process about revealing disability information". Riley and Hagger (2015) interviewed 10 people of various ages who had suffered from a traumatic brain injury. They identify six reasons for nondisclosure: fears of negative reactions from others, feelings of shame, avoidance of emotional upset about the incident causing the injury, feelings that others were not interested in their injury, perceptions that the stress of disclosing their injury to others outweighed the benefits and a desire to fit in as a person without a brain injury-or in other words, not wanting a traumatic brain injury to define them and to isolate them socially.…”
Section: Disability and Disclosurementioning
confidence: 99%
“…The general public can be rejecting and prejudicial in its response to brain injury and the difficulties that the person may have (i.e. stigmatizing attitudes and enacted stigma) (Jones, Jetten, Haslam, & Williams, 2012;Karlovits & McColl, 1999;Nochi, 1998;Riley & Hagger, 2015). For example, participants in the study by Riley and Hagger (2015) described being ridiculed by children in the street and by colleagues at work because of their disabilities.…”
Section: Stigmamentioning
confidence: 99%
“…stigmatizing attitudes and enacted stigma) (Jones, Jetten, Haslam, & Williams, 2012;Karlovits & McColl, 1999;Nochi, 1998;Riley & Hagger, 2015). For example, participants in the study by Riley and Hagger (2015) described being ridiculed by children in the street and by colleagues at work because of their disabilities. There is evidence of anticipated stigma (Baldwin, Powell, & Lorenc, 2011;Karlovits & McColl, 1999;Nochi, 1998;Riley, Brennan, & Powell, 2004;Riley & Hagger, 2015;Shorland & Douglas, 2010).…”
Section: Stigmamentioning
confidence: 99%
See 2 more Smart Citations